COVID-19 pandemic and psychological fatigue in Turkey - Morgul, Ebru (Int J Soc Psychiatry, 2020)
AIM: The aim of this study was to investigate the association between the COVID-19 pandemic and psychological fatigue as a mental health issue among the population of Istanbul, Turkey. PARTICIPANTS AND METHODS: This is a cross-sectional study conducted in Istanbul, Turkey, between March and June 2020, where a total of 4,700 persons were approached and 3,672 (78%) of participants (64.4% males and 35.6% females) completed the Knowledge Attitude Practices (KAP) and Fatigue Assessment Scale (FAS) questionnaires. RESULTS: In this study, 64.1% of participants were categorized as psychologically fatigued and 35.9% as normal. There was a significant difference between fatigued and normal participants with respect to age, educational level, occupational status, place of residence and number of family members (p < .001). Other differences related to knowledge of COVID-19 were symptoms, treatment, ways of spreading (p < .001), prevention by avoiding crowded places (p = .008) and isolation (p = .002). For attitudinal items, normal participants generally showed more positive attitudes than the fatigued in believing that COVID-19 will finally be controlled, satisfaction with preventive measures taken by the authorities, reporting suspected cases with symptoms and trusting that Turkey can overcome the COVID-19 pandemic (p < .001). Multivariate stepwise regression analysis indicated that level of education, avoiding going to crowded places, eye, nose and mouth organs are sensitive organs to the virus, keeping physical distance due to epidemic affect by COVID-19 virus, isolation and treatment of people reduce the spread of COVID-19 virus and 14-days period of time, COVID-19 is mainly transmitted through contact with the respiratory droplets of an infected person, occupational status, health education programme needed and antibody treatment variables were significantly associated with fatigue after adjusting for age, gender and income variables. CONCLUSION: The current study provides valuable information for policymakers and mental health professionals worldwide regarding associations between the mental health of individuals and the ongoing outbreak, COVİD-19.